The first transmembrane domain (TM1) of β2-subunit binds to the transmembrane domain S1 of α-subunit in BK potassium channels - Morera, Francisco J. (2012)
The BK channel is one of the most broadly expressed ion channels in mammals. In many tissues, the BK channel pore-forming α-subunit is associated to an auxiliary β-subunit that modulates the voltage- and Ca(2+)-dependent activation of the channel. Structural components present in β-subunits that are important for the physical association with the α-subunit are yet unknown. Here, we show through co-immunoprecipitation that the intracellular C-terminus, the second transmembrane domain (TM2) and the extracellular loop of the β2-subunit are dispensable for association with the α-subunit pointing transmembrane domain 1 (TM1) as responsible for the interaction. Indeed, the TOXCAT assay for transmembrane protein–protein interactions demonstrated for the first time that TM1 of the β2-subunit physically binds to the transmembrane S1 domain of the α-subunit.